2020
DOI: 10.1177/0022042620921363
|View full text |Cite
|
Sign up to set email alerts
|

Police Officers’ Views of Naloxone and Drug Treatment: Does Greater Overdose Response Lead to More Negativity?

Abstract: Police officers and emergency personnel are on the frontlines of the opioid crisis. This research examines police officer attitudes about naloxone administration, drug treatment, and their role in handling drug-related incidents through an online survey. Although officers view themselves as adequately trained in administering naloxone/Narcan, almost half (43%) believe there should be a limit on how often someone who overdoses receives Narcan and the majority (83%) view naloxone/Narcan as providing an excuse to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…For instance, Wagner et al (2016) found that officers reported positive attitudinal changes after receiving training on overdose and naloxone administration. However, more recently, Murphy and Russell (2020) reported that many police officers that administered naloxone frequently suffered from “compassion fatigue” and held stigmatizing attitudes toward persons who use opioids. Furthermore, a study conducted by Lowder and colleagues (2020) in Indianapolis indicated that individuals who experienced a police response to an overdose in which naloxone was administered were more likely to be arrested following the dispatch and had more subsequent nonfatal overdoses in the 2 years after the police administered the naloxone than individuals who had an EMT response and naloxone administration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Wagner et al (2016) found that officers reported positive attitudinal changes after receiving training on overdose and naloxone administration. However, more recently, Murphy and Russell (2020) reported that many police officers that administered naloxone frequently suffered from “compassion fatigue” and held stigmatizing attitudes toward persons who use opioids. Furthermore, a study conducted by Lowder and colleagues (2020) in Indianapolis indicated that individuals who experienced a police response to an overdose in which naloxone was administered were more likely to be arrested following the dispatch and had more subsequent nonfatal overdoses in the 2 years after the police administered the naloxone than individuals who had an EMT response and naloxone administration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has indicated that stigma may be one barrier to combating the opioid epidemic (Kruis & Choi, 2020; Kruis et al, 2020; Murphy & Russell, 2020). In fact, Formica and Colleagues (2018) argued that provider-based stigma among police officers may be the biggest barrier to implementing “deflection” programs where law enforcement officers serve as a connecting point between persons who experience an overdose and treatment providers in Massachusetts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations